FEATURES OF THE DEVELOPMENT OF INDIVIDUAL TAX LEGAL RELATIONS IN THE CONTEXT OF DIGITALIZATION - Ashurov Sherzod Rakhimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The development of digital technologies directly affects changes in the structure of tax legal relations. The significant transformative impact of digitalization is already showing the scientific community and specialists in tax legal relations the prospects for the evolution of tax legal relations themselves. At the same time, tax legal relations have a significant number of varieties and arise in connection with the payment and collection of taxes, the implementation of tax control, pre-trial settlement of tax disputes and in other cases. The central place is occupied by legal relations arising in connection with the payment of tax.